2007
DOI: 10.1002/ceat.200700066
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of a Lignin Model Compound under Hydrothermal Conditions

Abstract: Lignin, which is the second most abundant polymeric aromatic organic substance in wood biomass after cellulose, and contains many oxygen-based functional groups, has been proposed as an alternative source of chemical compounds. Guaiacol, a model compound for lignin, was reacted in supercritical water using a batch-type reactor at temperatures of 653-673 K and various pressures under an argon atmosphere. The effects of temperature and reaction time at the same pressure were combined into a single severity param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(50 citation statements)
references
References 27 publications
5
41
0
Order By: Relevance
“…As a lignin model component, guaiacol conversion in supercritical water has been examined by Wahyudiono et al [48,49] and Dileo et al [50]. In addition, Yong and Matsumura [34,35] investigated the lignin decomposition pathway through guaiacol.…”
Section: Monomersmentioning
confidence: 99%
“…As a lignin model component, guaiacol conversion in supercritical water has been examined by Wahyudiono et al [48,49] and Dileo et al [50]. In addition, Yong and Matsumura [34,35] investigated the lignin decomposition pathway through guaiacol.…”
Section: Monomersmentioning
confidence: 99%
“…Table 2 shows the peak areas of 2-methoxyphenol (retention time (RT) = 6.26 min), 4-ethyl-2-methoxyphenol (RT = 7.78 min), and 2,6-dimethoxyphenol (RT = 8.3 min) increased with increased reaction temperatures. Interestingly, the study of Wahyudiono and colleagues showed that higher temperatures were conducive to conversion of the methoxyl aromatic products (Wahyudiono et al 2007). …”
Section: Gc-ms Analysis Of Ho and Wsomentioning
confidence: 99%
“…The substantial presence of 4-methylphenol and 4-ethylphenol in the XRL could also be caused by a higher probability for the formation and coupling of methyl-radicals and phenyl radicals from H-type units. Additionally, a lower level of G-type compounds formed from lignin ether-bond hydrolysis can easily lead to polyhydroxy phenol by dealkylation reactions, as shown in past work (Kanetake et al 2007;Toor et al 2011). Thus, catechol compounds can be obtained from guaiacol.…”
Section: Quantitative Analysis Of Predominant Phenolic Compoundsmentioning
confidence: 89%